Pengembangan LKPD dengan Strategi Pembelajaran REACT pada Materi Sistem Pertidaksamaan Linear - Dyah Ayu Nur Aini; Aprillia Intan Nur Cahya; Fhadilla Riski Aryani; Raisa Nur Azizah (FKIP, Universitas Palangka Raya, 2025)
The research carried out produced Student Worksheets (LKPD) based on the REACT learning strategy on linear inequalities material. The development method used is the Instructional Development Model (MPI) with the steps: identification, development and carrying out formative evaluation and revision. This worksheet is designed by utilizing the REACT (Relating, Experiencing, Applying, Cooperating and Transferring) learning strategy, which aims to stimulate students' interest and involvement and strengthen understanding of the concept of systems of linear inequalities. The evaluation was carried out through validation tests by material experts, media experts and mathematics teachers. The results of the research show that the LKPD developed is suitable for use as mathematics learning material.